American rebel [compact disc] - Nelson, Willie, 1933- (Goldenlane Records, a division of Cleopatra Records, 2022)
A hand-selected compilation of early '60s tracks from national treasure and one of the most iconic American vocalists, songwriters and rebels, Willie Nelson!